Formula for Success According to TIMSS or the Subliminal Decay of Jurisdictional Educultural Integrity? - Puk, Tom (Alberta Journal of Educational Research, 1999)
The results of international testing such as those found in the Third International Mathematics and Science Study (TIMSS) are often used to develop curriculum policy in a jurisdiction without questioning the significance of the scores and without realizing the connotative influences contained in these tests. This article compares the teaching practices of science teachers in Ontario, a modest-scoring jurisdiction, with the teaching practices of teachers in Alberta and Singapore, both high-scoring jurisdictions. An implicit "formula for success" for scoring high in TIMSS is identified. However, the main message of the article is that when developing curriculum policy, jurisdictions should instead first consider the desired local image of the educated person rather than allowing international test results to redefine an educational system that may be dysfunctional in the long term. The subliminal decay of jurisdictional educultural integrity may be a by-product of using international test results to determine local curricular policy.